Renaissance polyphony - Fitch, Fabrice 1967- (Cambridge introductions to music, 2020)
This engaging study introduces Renaissance polyphony to a modern audience. It helps readers of all ages and levels of experience make sense of what they are hearing. How does Renaissance music work? How is a piece typical of its style and type; or, if it is exceptional, what makes it so? The makers of polyphony were keenly aware of the specialized nature of their craft. How is this reflected in the music they wrote, and how were they regarded by their patrons and audiences? Through a combination of detailed, nuanced appreciation of musical style and a lucid overview of current debates, this book offers a glimpse of meanings behind and beyond the notes, be they playful or profound. It will enhance the listening experience of students, performers and music lovers alike